Willingness to adopt personal biosecurity strategies on thoroughbred breeding farms: Findings from a multi-site pilot study in Australia's Hunter Valley - Thompson, Kirrilly; Taylor, Joanne; Mendez, Diana; Chicken, Catherine; Carrick, Joan; Durrheim, David N. (Frontiers in Veterinary Science, 2022)
There are almost 9,500 full-time employees in Australia’s thoroughbred horse breeding industry. During foaling, they can be exposed to bodily fluids and mucous membranes that have risks for zoonotic disease. These risks can be mitigated through personal biosecurity strategies. The aim of this study was to identify which personal biosecurity strategies were more or less likely to be adopted by workers. Seventeen participants representing 14 thoroughbred breeding farms and three equine veterinary practices in Australia’s largest thoroughbred breeding region trialled up to 16 stakeholder-nominated personal biosecurity strategies over the 2021 foaling season. The strategies encompassed personal protective equipment (PPE), zoonotic disease awareness, policies and protocols, supportive environments, and leadership. Strategy adoption was monitored through three repeated self-audit surveys designed around the Transtheoretical Model of change (TTM) and findings were reviewed in exit interviews. For all survey waves in aggregate, 13 strategies were practised by at least 50% of participants. Participants were most likely to use a ready-made foaling box (98%), communicate the message that PPE usage is a personal responsibility (94.1%) and use ready-made PPE kits (88.2%). However, 31.4% had no intention of doing practice sessions and/or dummy runs for PPE use and 27.5% had no intention of using a buddy system on farm/practice to check use of PPE. Whilst these rates indicate workers’ willingness to adopt and maintain personal biosecurity strategies, they indicate capacity for more practices to be implemented more often. Overall, findings highlight the need for personal biosecurity interventions to be sensitive to the demands of the annual thoroughbred breeding calendar, the size of the breeding operation and the availability of skilled staff.